Sensitive spectrophotometric assay of simvastatin in pharmaceuticals using permanganate - Kalsang Tharpa; Kanakapura Basavaiah; Nagaraju Rajedraprasad; Kanakapura Basavaiah Vinay; Salmara Ganeshbhat Hiriyanna (Universidade de São Paulo, 2010)
Two simple, sensitive, selective and inexpensive spectrophotometric methods are described for the determination of simvastatin (SMT) in bulk drug and in tablets using permanganate as the oxidimetric reagent. In method A, SMT is treated with a measured excess of permanganate in acetic acid medium and the unreacted oxidant is measured at 550 nm, whereas in method B the reaction is carried out in alkaline medium and the resulting manganate is measured at 610 nm. In method A, the amount of permanganate reacted corresponds to the SMT content and the absorbance is found to decrease linearly with the concentration; and in method B, the absorbance increases with concentration. The working conditions of assays were optimized, and the methods were validated according to the current ICH guidelines. Under optimum conditions, SMT could be assayed in the concentration ranges, 1.47 - 17.67x10-5 and 2.27 - 27.18 x10-6 mol/L by method A and method B, respectively. The calculated molar absorptivities are 3.2 x 10³ and 2.5 x 10(4) L/mol/cm for method A and method B, respectively with corresponding Sandell sensitivity values of 0.0387 and 0.0178 μg/cm². The limits of detection (LOD) and quantification (LOQ) have also been reported. Accuracy and precision for the assay were determined by calculating the intra-day and inter-day at three concentrations; the intra-day RSD was < 2% and the accuracy was better than 2.15 % (RE). The methods were applied successfully for the determination of SMT in tablet dosage form with a high percentage of recovery, good accuracy and precision, and without measurable interference by the excipients. The accuracy was further ascertained from placebo and synthetic mixture analysis and also from the spike-recovery method. Dois métodos espectrofotométricos simples, sensíveis, seletivos e baratos são descritos para a determinação de sinvastatina (SMT) a granel e em comprimidos, utilizando permanganato como reagente oxidimétrico. No método A, a SMT é tratada com excesso conhecido de permanganato em meio de ácido acético e o oxidante que não reage é medido a 550 nm, enquanto no método B, a reação é efetuada em meio alcalino e o manganato resultante é medido a 610 nm. No método A, a quantidade de permanganato que reage corresponde ao conteúdo de SMT e a absorbância diminui linearmente com o aumento da concentração; no método B, a absorbância aumenta com o aumento da concentração. As condições de trabalho do ensaio foram otimizadas e os métodos, validados de acordo com as normas do ICH. Sob condições ótimas, a SMT pode ser ensaiada nas faixas de concentração de 1,47- 17,67x10-5 e de 2,27-27,18 x10-6 mol/L pelo método A e B, respectivamente. As absortividades molares calculadas são 2 x 10³ e 2,5 x 10(4) L/ mol/cm, respectivamente, para os métodos A e B, com os valores correspondentes de sensibilidade de Sandell de 0,0387 e 0,0178 μg/cm². Os limites de detecção (LOQ) também foram relatados. A exatidão e a precisão do ensaio foram determinadas pelo cálculo de três concentrações intra- e inter-dia; a RSD intra-dia foi <2% e a exatidão foi melhor que 2,15% (RE). Os métodos foram aplicados com sucesso à determinação de SMT em comprimidos com alta porcentagem de recuperação, boa exatidão e precisão e sem interferência mensurável dos excipientes. A exatidão foi posteriormente determinada no placebo e na mistura sintética e, também, pelo método de spike recovery.